1948
DOI: 10.1104/pp.23.4.403
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Deficiency and Excess in Guayule. Ii. Cation-Anion Balance in the Leaves

Abstract: In many plants the potassium contained in the tissues is almost completely water soluble (3,15,16, 18, 19,32) It is generally supposed that much of the potassium present in plants is in the form of salts of organic acids and that these acids and their salts constitute principal components of the buffer systems. A relationship between the total organic acids and the excess of cations over inorganic anions in tobacco leaves of different ages and base composition was shown by PUCHER, VICKERY, and WAKEMAN (22). PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

1948
1948
1977
1977

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…When guayule leaves from the intermediate potassium treatments are used as a basis for comparison, high potassium leaves were relatively high in citric acid (9). Malic acid did not accumulate in high potassium leaves.…”
Section: Nitrogenous Fractions Of the Leavesmentioning
confidence: 99%
See 2 more Smart Citations
“…When guayule leaves from the intermediate potassium treatments are used as a basis for comparison, high potassium leaves were relatively high in citric acid (9). Malic acid did not accumulate in high potassium leaves.…”
Section: Nitrogenous Fractions Of the Leavesmentioning
confidence: 99%
“…These workers have also shown that of the total free reducing sugars, the amounts of free nion-fructose sugars are always greater than the amounits of free fructose in spite of the fact that the chief reserve carbohydrates in guayule are polymers of fructose, levulins and inulin. The coniditions of the present experiment were not conducive to large accumulations of inulin, or higher polymer levulins, insofar as the experiment consisted of a phase of rapid growth.So far as the writers are aware, no detailed study has been made of the nitrogenous fractions in guayule.Effects of potassium supply upon growth responses and mineral contents of guayule plants and upon cation and inorganic and organic aniion contents of the leaves have been reported (8,9). In this paper are considered carbohydrate and nitrogenous fractions in tissues of the same plants.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that some anion other than an organic acid radical is involved. For example, Cooil (5) has shown that bicarbonate in guayule leaves can function in cation balancing. In any event, this would not explain the disproportionate increase of malate over total organic acid.…”
Section: Methodsmentioning
confidence: 99%
“…Since roots may absorb cations and anions at unequal rates from single salt solutions, they must therefore have at their disposal mechanisms for maintaining cation-anion equivalency. In recent years, the role of organic acid metabolism in relation to the mainteilance of cation-anion balance have been investigated by Pucher, Vickery and Wakeman (15), Ulrich (17), Overstreet, Broyer, Isaacs and Delwiche (11), Pierce and Appleman (13), Burstrom (2), Cooil (5), and others.…”
mentioning
confidence: 99%